Aspergillus endocarditis in the recent years, report of cases of a multicentric national cohort and literature review. Issue 3 (12th January 2022) - Valerio, Maricela; Camici, Marta; Machado, Marina; Galar, Alicia; Olmedo, Maria; Sousa, Dolores; Antorrena‐Miranda, Isabel; Fariñas, Maria Carmen; Hidalgo‐Tenorio, Carmen; Montejo, Miguel; Vena, Antonio; Guinea, Jesús; et al.
Abstract: Objectives: (1) To describe the incidence, clinical characteristics, treatment and outcome of Aspergillus Endocarditis (AE) in a nationwide multicentric cohort (GAMES). (2) To compare the AE cases of the GAMES cohort, with the AE cases reported in the literature since 2010. (3) To identify variables related to mortality. Methods: We recruited 10 AE cases included in the GAMES cohort (January 2008‐December 2018) and 51 cases from the literature published from January 2010 to July 2019. Results: 4528 patients with infectious endocarditis (IE) were included in the GAMES cohort, of them 10 (0.2%) were AE. After comparing our 10 cases with the 51 of the literature, no differences were found. Analysing the 61 AE cases together, 55.7% were male, median age 45 years. Their main underlying conditions were as follows: prosthetic valve surgery (34.4%) and solid organ transplant (SOT) (19.7%). Mainly affecting mitral (36.1%) and aortic valve (29.5%). Main isolated species were as follows: Aspergillus fumigatus (47.5%) and Aspergillus flavus (24.6%). Embolisms occurred in 54%. Patients were treated with antifungals (90.2%), heart surgery (85.2%) or both (78.7%). Overall, 52.5% died. A greater mortality was observed in immunosuppressed patients (59.4% vs. 24.1%, OR = 4.09, 95%CI = 1.26–13.19, p = .02), and lower mortality was associated with undergoing cardiac surgery plus azole therapy (28.1% vs. 65.5%, OR = 0.22, 95%CI = 0.07–0.72, p = .01). Conclusions: AE accounts for 0.2% of all IE episodes of a national multicentric cohort, mainly affecting patients with previous valvular surgery or SOT recipients. Mortality remains high especially in immunosuppressed hosts and azole‐based treatment combined with surgical resection are related to a better outcome.